Dictatorship in history and theory : Bonapartism, Caesarism, and totalitarianism - Baehr, Peter; Richter, Melvin, 1921-2020 (Publications of the German Historical Institute., 2004)
Bringing together the work of historians and political theorists to examine the complex relationships among nineteenth century democracy, nationalism, and authoritarianism, this study pays special attention to the careers of Napoleon I and III, and of Bismarck. An important contribution is consideration of not only the momentous episodes of coup d'etat, revolution, and imperial foundation which the Napoleonic era heralded, but also the contested political language with which these events were described and assessed. Political thinkers were faced with a battery of new terms--"Bonapartism," "Caesarism," and "Imperialism" etc ... --with which to define their era